2022
DOI: 10.1021/acs.jpca.2c02032
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a Reliable Density Functional for Molecule–Environment Interactions, Found B97M-V/def2-mTZVP

Abstract: In the present study, we have examined density functional theory methods for the calculation of the interaction energy between a small molecule and its environment. For simple systems such as a neutral solute in a neutral solvent, good accuracy can be attained using low-cost "3c" methods, in particular r 2 SCAN-3c. When part(s) of the system is charged, the accurate computation of the interactions is more challenging. In these cases, we find the B97M-V/def2-mTZVP method to agree well with reference values; it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 68 publications
0
16
1
Order By: Relevance
“…This setup is based on the B97 GGA functional and includes D3 with a three-body contribution and a short-range bond length correction. The modified, stripped-down triple- ζ basis, def2-mTZVP 50 is used in the setup. For the relatively large tetracobalt complex 5 , the crystal structure with the optimized positions for hydrogen atoms was used for the analysis of unrestricted corresponding orbitals and spin density.…”
Section: Methodsmentioning
confidence: 99%
“…This setup is based on the B97 GGA functional and includes D3 with a three-body contribution and a short-range bond length correction. The modified, stripped-down triple- ζ basis, def2-mTZVP 50 is used in the setup. For the relatively large tetracobalt complex 5 , the crystal structure with the optimized positions for hydrogen atoms was used for the analysis of unrestricted corresponding orbitals and spin density.…”
Section: Methodsmentioning
confidence: 99%
“…We further refine the energies using the B97M-V functional in conjunction with the def2-mSVP basis set 64 , as implemented in Orca 65 . The B97M-V method has recently been shown to yield accurate binding energies between an enzyme and its substrate for a wide range of systems 66 . The geometric counter poise (gCP) correction 67 , parameterized for the def2-mSVP basis set, is applied to provide an accuracy that is comparable to that at the complete-basis-set limit.…”
Section: Methodsmentioning
confidence: 99%
“…In 2005, a cubic water box containing 216 molecules was simulated using DC-based and HF-type SE methods . The DFTB method was applied along with the DC method in the 2000s to analyze the structure, mechanics, and dynamics of protein, amylose chain, and bulk water systems. In the last several years, more than 30 computational studies have been reported by utilizing the DCDFTBMD (or its predecessor) program introduced in section . , ,,, ,, ,,,, …”
Section: Illustrative Applicationsmentioning
confidence: 99%